2009
DOI: 10.1128/jvi.02378-08
|View full text |Cite
|
Sign up to set email alerts
|

Protein Array Identification of Substrates of the Epstein-Barr Virus Protein Kinase BGLF4

Abstract: A conserved family of herpesvirus protein kinases plays a crucial role in herpesvirus DNA replication and virion production. However, despite the fact that these kinases are potential therapeutic targets, no systematic studies have been performed to identify their substrates. We generated an Epstein-Barr virus (EBV) protein array to evaluate the targets of the EBV protein kinase BGLF4. Multiple proteins involved in EBV lytic DNA replication and virion assembly were identified as previously unrecognized substra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
91
1
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 66 publications
(97 citation statements)
references
References 53 publications
4
91
1
1
Order By: Relevance
“…Interestingly, BGLF5 has recently been shown to be a substrate for phosphorylation by BGLF4 (53). Whether this is the case in replicating cells is still unknown, but the 293/ ⌬BGLF4 mutant or 293/⌬⌬BG4/5 double mutant should help in clarifying this issue.…”
Section: Vol 83 2009 Regulation Of Ebv Protein Synthesis 10889mentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, BGLF5 has recently been shown to be a substrate for phosphorylation by BGLF4 (53). Whether this is the case in replicating cells is still unknown, but the 293/ ⌬BGLF4 mutant or 293/⌬⌬BG4/5 double mutant should help in clarifying this issue.…”
Section: Vol 83 2009 Regulation Of Ebv Protein Synthesis 10889mentioning
confidence: 99%
“…BGLF4 colocalizes during lytic replication with BMRF1 (also called early protein [EA-D] or DNA polymerase processivity factor) in replication compartments. These and other viral proteins such as BGLF5, but not BZLF1, were recently confirmed as being BGLF4 targets using an extensive EBV protein array (53). In addition, BGLF4 was found to interact with EBNA1 (53).…”
mentioning
confidence: 99%
“…Indeed, half of the EBV-PK targets identified by a protein array in a recent study were also found to be in vitro substrates for the cellular kinase CDK1/cyclin B (63). Overexpression of EBV-PK in cells has been shown to result in phosphorylation of a number of different cellular proteins, including the cell cycle regulatory proteins p27 (19) and pRB (C. V. Kuny and R. F. Kalejta, unpublished data); nuclear lamin A/C (32); interferon regulatory factor 3 (IRF3) (54); cellular translational elongation factor 1␦ (24,26); MCM4 (part of the MCM4-MCM6-MCM7 cellular replication origin binding complex) (29); and histone protein H2AX (52).…”
mentioning
confidence: 99%
“…We previously used protein microarrays to identify substrates of human kinases, monitor changes in the human phospho-proteome, identify kinases that phosphorylate viral proteins, and identify cellular and viral substrates of viral kinases (61)(62)(63)(64)(65). We have now adapted this ap-proach to identify proteins that are potentially ERK-primed GSK-3 substrates.…”
Section: Establishment Of the Screening Assaymentioning
confidence: 99%